﻿Amentotaxus × hybridia (Taxaceae), a new natural Amentotaxus hybrid from southeast Yunnan province, China - Lian-Ming Gao; Gui-Liang Zhang; Zhi-Qiong Mo; Philip Thomas (PhytoKeys, 2023)
During floristic surveys of Taxaceae in Hekou County, Yunnan Province, China, a putative natural hybrid between A. yunnanensis H.L. Li and A. hekouensis L.M. Gao was collected. Morphological and molecular evidence confirms its status as a natural hybrid. Amentotaxus × hybridia L.M. Gao has linear or linear-lanceolate leaves 6–13 cm × 1.0–1.5 cm, white stomatal bands with 34–40 rows on abaxial side, 2.5–3.5 mm, slightly wider than leaf margins; 3–6 seeds borne at the base of the branchlet, peduncle 1.3–1.6 cm long with 3–4 rows of persistent basal bracts.